Mutants of Pachysolen tannophilus with Improved Production of Ethanol from d-Xylose - Lee, Hung (1986)
The conversion of d-xylose to ethanol by the yeast Pachysolen tannophilus is relatively inefficient in batch culture. The inefficiency has been attributed in part to concurrent utilization of ethanol in the presence of appreciable concentrations of d-xylose and to the formation of xylitol and other by-products. To increase the concentration of ethanol accumulated in batch cultures, UV-induced mutants of P. tannophilus were selected on the basis of diminished growth on ethanol. Eleven independent mutant loci that conferred the ethanol-defective phenotype were identified. Three led to a greater yield and volumetric rate of production of ethanol than the wild type. One also produced less xylitol and was characterized by a deficiency in activity for malate dehydrogenase.